Treatment of chronic hepatitis C by cepeginterferon alpha-2b in combination to ribavirin - M. V. Mayevskaya; O. O. Znoyko; Ye. A. Klimova; S. L. Maximov; S. N. Kizhlo; N. A. Petrochenkova; F. I. Nagimova; Yu. N. Linkova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
Aim of investigation. Comparative study of efficacy and safety of Algeron in dozes of 1,5 and 2,0 mkg/kg and PegIntron in combination to ribavirin within combined mode of treatment of patients with chronic hepatitis C (CHC) with subsequent assessment of therapeutic doze of Algeron.Material and methods. In open randomized «noninferiority» clinical study of II–III phase 150 previously untreated by interferon adult CHC patients (genotypes 1, 2, 3) were randomized in three medical groups: Algeron 1,5 mkg/kg, Algeron 2,0 mkg/kg and active control group — PegIntron 1,5 mkg/kg. All patients received ribavirin 800-1400 mg/day for 24-48 wks in relation to genotype. Early virologic response (EVR) rate was used as a primary endpoint of efficacy. Intentto-treat the analysis was applied at rating of obtained results.Results. The comparative analysis has demonstrated, that EVR at the 12-th week in group of Algeron 1,5 mkg/kg was observed in 100 % of patients with genotypes 2/3 and in 88,5% of patients with genotype 1. In Algeron 2,0 mkg/kg group it was registered at 95,7 and 92,6 % of patients respectively, in control group – in 95,5 and 82,1% (р> 0,05 in comparison of all scores between groups). As no distinctions in Algeron efficacy were revealed, at more favorable safety profile of low doze, the therapeutic doze of 1,5 mkg /kg/wk has been chosen. After the first 12 wks of treatment all patients of the 1-st and 2-nd groups received Algeron in the chosen doze of 1,5 mkg/kg up to termination of the treatment course. Therefore the response at the end of treatment (direct virologic response, DVR) and sustained virologic response (SVR) were estimated for patients of the 1-st and 2-nd groups in common (n=100). Among patients with HCV 2/3 genotypes, receiving Algeron, DVR was observed in 93,6%, in control group – in 81,8%, in patients with the 1-st virus genotype — in 83 and 71,4 % of cases respectively (р>0,05 at comparison of all scores between groups). In patients with 2/3 genotypes HCV, at Algeron therapy, SVR was reached in 83 % of cases, in PegIntron group — in 81,8 %. In patients with the 1-st virus genotype it was observed in 67,9 and 57,1 % respectively (p> 0,05). The adverse events were registered during treatment by Algeron, in dose-dependent manner, however their frequency had did not exceed that in patients receiving standard PegIntron dozes.Conclusions. Study results prove high efficacy and safety of Algeron in suppression of hepatitis C virus replication and allow to recommend its application at previously untreated patients with CHC in a doze of 1,5 mkg/kg/wk for 24-48 wks in relation to genotype HCV.